Arm circumference as an index of protein-energy malnutrition in urban Filipino infants aged 6- to 11- months - Sanchez, Liza E. (1997)
Arm circumference has not been widely used as an indicator of malnutrition because of its limited usefulness in assessing different populations. The utility of arm circumference as a screening tool for malnutrition was assessed in an anthropometric survey of 942 urban Filipino children 6- to 11-months old. Age-independence and correlation with standard anthropometric indices (weight-for-age, weight-for-height, and height-for-age) were determined. Furthermore, validity of arm circumference was evaluated using standard anthropometric indices ( -2 SD) as criteria to define true malnutrition. Arm circumference was found to be age-independent (r, specificity=85, positive predictive value (PPV)=52) were found using the weight-for-age standard ( -2 SD) and the 13.5 cm arm circumference cut-off. With such sensitivity and specificity levels, there was a corresponding high proportion of false negatives. In addition, the PPV was 52. These findings show that arm circumference does not perform well as a screening test. Moreover, the use of weight-for-age as the gold standard poses important limitations since this index fails to distinguish between present and past malnutrition. Though arm circumference was not proven to be valid in this setting, it may still be of value for certain applications. Arm circumference seemed to perform nearly as much as height- and weight-based measurements. Simutaneous assessment of arm circumference with other indicators would provide an independent measure of nutritional status for minimal additional effort.